The impact of digital transformation on the micrologistic system, and the open innovation in logistics - Nikolaj Ivanovič Didenko; Djamilia Skripnuk; Kseniia Kikkas; Olga Kalinina; Eryk Kosinski (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This paper investigates the effects of digital production and information technologies on the development of logistic systems of different kinds: megalogistic, macrologistic, and micrologistic. The notions of a logistic system and types of logistic systems imply that logistics is considered in its broad sense as a modern methodology for managing all types of flows that appear in the process of socioeconomic activities of society and business: material, information, energy, financial and labor flows. The methodology discussed in this paper gives the answer to the question of what impact digital production and information technologies have on the development of various types of logistic systems. The methodology includes building a mathematical model in which the endogenous variables of the model reflect the resulting variables of the logistic system, while the exogenous variables reflect digital production and information technologies. The mathematical model is a system of interdependent dynamic econometric equations. Each equation is an autoregressive distributed lags model. In the model, the current values of an endogenous variable depend on their previous values, as well as on the current and previous values of other endogenous and exogenous variables. The novelty of the research is in the developed methodology for a comprehensive assessment of the impact made by digitalization on a totality of the interrelated and interdependent resulting indicators of the logistic system. A comprehensive assessment of the impact made by digitalization on a totality of interrelated and interdependent indicators of the logistic system is understood as a change in the indicators of the logistic system due to the effect of digitalization. The proposed methodology for a comprehensive assessment was empirically tested for Salesforce company.
Keywords: 650; digital economy; digital economy technology; Industry 4.0; innovation; logistic system; model of Interdependent econometric Equations; open innovation